Sural nerve injury in familial amyloid polyneuropathy: MR neurography vs clinicopathologic tools - Hayes, Jennifer; Sahm, Felix; Hegenbart, Ute; Purrucker, Jan; Kimmich, Christoph; Schönland, Stefan; Hund, Ernst; Heiland, Sabine; Kristen, Arnt; Pham, Mirko; Bendszus, Martin; Weiler, Markus (Neurology, 2017)
Objective: To detect and quantify lesions of the small-caliber sural nerve (SN) in symptomatic and asymptomatic transthyretin familial amyloid polyneuropathy (TTR-FAP) by high-resolution magnetic resonance neurography (MRN) in correlation with electrophysiologic and histopathologic findings. Methods: Twenty-five patients with TTR-FAP, 10 asymptomatic carriers of the mutated transthyretin gene (mutTTR), and 35 age- and sex-matched healthy controls were prospectively included in this cross-sectional case-control study. All participants underwent 3T MRN with high-structural resolution (fat-saturated, T2-weighted, and double-echo sequences). Total imaging time was z45 minutes per patient. Manual SN segmentation was performed from its origin at the sciatic nerve bifurcation to the lower leg with subsequent evaluation of quantitative microstructural and morphometric parameters. Additional time needed for postprocessing was z1.5 hours per participant. Detailed neurologic and electrophysiologic examinations were conducted in the TTR group. Results: T2 signal and proton spin density (r) reliably differentiated between TTR-FAP (198.0 6 13.3, 429.6 6 15.25), mutTTR carriers (137.0 6 16.9, p 5 0.0009; 354.7 6 21.64, p 5 0.0029), and healthy controls (90.0 6 3.4, 258.2 6 9.10; p , 0.0001). Marked differences between mutTTR carriers and controls were found for T2 signal (p 5 0.0065) and r (p , 0.0001). T2 relaxation time was higher in patients with TTR-FAP only (p 5 0.015 vs mutTTR carriers, p 5 0.0432 vs controls). SN caliber was higher in patients with TTR-FAP vs controls and in mutTTR carriers vs controls (p , 0.0001). Amyloid deposits were histopathologically detectable in 10 of 14 SN specimens. Conclusions: SN injury in TTR-FAP is detectable and quantifiable in vivo by MRN even in asymptomatic mutTTR carriers. Differences in SN T2 signal between controls and asymptomatic mutTTR carriers are derived mainly from an increase of r, which overcomes typical limitations of established diagnostic methods as a highly sensitive imaging biomarker for early detection of peripheral nerve lesions.